2008
DOI: 10.1037/0096-1523.34.2.340
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive control: Dynamic, sustained, and voluntary influences.

Abstract: The cost of incongruent stimuli is reduced when conflict is expected. This series of experiments tested whether this improved performance is due to repetition priming or to enhanced cognitive control. Using a paradigm in which Word and Number Stroop alternated every trial, Experiment 1 assessed dynamic trial-to-trial changes. Incongruent trials led to task-specific reduction of conflict (trial n ϩ 2) without cross-task modulation (trial n ϩ 1), but this was fully explained by repetition priming. In contrast, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
102
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(115 citation statements)
references
References 51 publications
11
102
3
Order By: Relevance
“…In addition, remember that our interval between the stimuli and the duration of the stimuli on the screen are closer to those of Mayr et al (2003) and Hommel (1998) and others have not found SCE when pure replicas are removed from the analysis Nieuwenhuis et al, 2006;Wendt et al, 2006). Therefore, the presence of SCE reinforces the idea that the SCE is due mainly to the presence of conflict (Vergruggen, Notebaert, Liefooghe & Vandierendock, 2003, Fernández-Duque & Knight, 2008Notebaert et al, 2006). However, there is a decrease of the SCE by eliminating pure replicas, which could support, in part, the points of view of Mayr et al (2003) and Hommel (1998).…”
Section: Discussionsupporting
confidence: 52%
“…In addition, remember that our interval between the stimuli and the duration of the stimuli on the screen are closer to those of Mayr et al (2003) and Hommel (1998) and others have not found SCE when pure replicas are removed from the analysis Nieuwenhuis et al, 2006;Wendt et al, 2006). Therefore, the presence of SCE reinforces the idea that the SCE is due mainly to the presence of conflict (Vergruggen, Notebaert, Liefooghe & Vandierendock, 2003, Fernández-Duque & Knight, 2008Notebaert et al, 2006). However, there is a decrease of the SCE by eliminating pure replicas, which could support, in part, the points of view of Mayr et al (2003) and Hommel (1998).…”
Section: Discussionsupporting
confidence: 52%
“…Mayr et al, 2003;Nieuwenhuis, et al, 2006;Wendt, Kluwe, & Peters, 2006) and in the Stroop task (e.g. Fernandez-Duque & Knight, 2008). Others, however, showed sequential eVects in interference tasks even when repetition priming could be ruled out (Akçay & Hazeltine, 2007;Freitas, Bahar, Yang, & Banai, 2007;Kerns et al, 2004;Notebaert, Gevers, Verbruggen & Liefooghe, 2006;Notebaert & Verguts, 2007;Ullsperger, Bylsma & Botvinick, 2005;Wühr & Ansorge, 2005).…”
Section: Introductionmentioning
confidence: 94%
“…In contrast, there is no published evidence that the list-wide proportion congruence manipulation stimulates use of a list-wide control mechanism that affects the magnitude of Stroop interference, independently of item-specific influences (but see Fernandez-Duque & Knight, 2008, for evidence of a sustained control mechanism in a task-switching Stroop paradigm). Thus, it might be reasoned that it is time to abandon the concept of list-wide control.…”
mentioning
confidence: 90%